A Case Study with Hofstede’s Culture: Working Performance of Chinese Expatriates in Dubai - Wenchang, Chen; Vasudevan, Asokan; Arumugam, Vasumathi; Zhang, Jin; Balakrishnan, Rajani; Rusuli, Muhamad Saufi Che (Journal of Ecohumanism, 2024)
This study investigates the working performance of Chinese expatriates in Dubai through the lens of Hofstede's cultural dimensions. It discusses the differences in culture between China and the United Arab Emirates (UAE) and how they affect the productivity of foreign workers. The theoretical framework for examining these cultural effects is Hofstede's model, which has six dimensions: power distance, individuality vs. collectivism, masculinity vs. femininity, uncertainty avoidance, long-term vs. short-term orientation, and indulgence vs. restraint. A questionnaire survey was used to gather information about the attitudes, values, and views of fifty Chinese expatriates in Dubai regarding Hofstede's cultural dimensions and work performance. 96% of the responses were valid, and 48 could be used after 2 were rejected for insufficient context. The studies revealed that power distance is highly related to Chinese expatriates' working performance in Dubai. On the other hand, individualism, long-term orientation, masculinity, uncertainty avoidance, and indulgence did not significantly affect the results. The performance of Chinese expatriates in the Middle East is of special interest to researchers studying cross-cultural management. It emphasizes how crucial cultural awareness and adaptation are for foreign workers and businesses in multicultural settings.